Italian and French prints in the Dominican library in Różanystok: A contribution to the study of the dissemination of books in Europe in the 17th and 18th centuries - Katarzyna Zimnoch (Roczniki Biblioteczne)
This paper aims to explore the influx of Italian and French prints into the Polish-Lithuanian Commonwealth, which illustrates the dissemination of books in Europe in the 17th and 18th centuries. The case study focuses on the book collection at the Dominican monastery in Różanystok, situated at the border of the Crown of the Kingdom of Poland and the Grand Duchy of Lithuania. The research reported on in this paper was mainly based on the handwritten inventories of the Dominican library from 1828 and 1846 and involved analysing the book collection based on the date and place of publication of the prints. Forty-seven Italian prints were identified, accounting for 8.07% of the entire collection; they primarily came from printing houses in Rome and Venice. Ten volumes, that is, 1.72% of the library holdings, stemmed from French printing houses in Lyon. The data were compared with the analogous figures for the Dominican book collections in Borek Stary, Samogitian Calvary, Lviv, Paparčiai and Wrocław. The research helps to identify the libraries in Central and Eastern Europe where the publishing production of Italian and French printers arrived. Furthermore, the paper sheds light on the transfer channels through which cultural and religious content from printing hubs spread in Europe in the timeframe under research.